Assessment of soft profile characteristics in Amazonian youngsters with normal occlusion - Wilson Maia de Oliveira Junior (Dental Press Editora, 2012)
OBJECTIVE: The present study aimed to determine from a sample of Amazonian youngsters, with normal occlusion, the mean values for soft profile characteristics using cephalometric radiographs obtained in lateral norm. METHODS: The cephalometric radiographs of the 30 youngsters, being 15 males and 15 females, with mean age of 21.6 years old, were assessed. For statistical analysis, central tendencies and dispersion measurements (mean and standard deviation) were used and, for both the comparison of the mean values of males and females and the correlations between the measurements of the soft profile and bony profile, the unpaired Student's t-test was applied. RESULTS AND CONCLUSION: After obtaining statistical data, parameters were set based on the cephalometric norms regarding the specialized literature, revealing that all variables presented a normal distribution pattern. There was sexual dimorphism for the following measurements: ANB, NAP, ANS-Me, N-ANS, Sn'-Me', and N'-SN'. Norms were determined for all the assessed measurements. Statistical differences were observed between the norm found in the present study and those found in the specialized literature.